Freedom. Spain : information bulletin of the C.N.T. and F.A.I. No. 1 - F.A.I. (Organization : Spain); Nettlau, Max, 1865-1944 (Freedom Publication Committee (London, England))
1936-08 SA03-01-003 15/3/8/236(iii)